Continuity and Change in the American Family. - Casper, Professor Lynne M. M. (SAGE Publications, 2001)
Continuity and Change in the American Family engages students with issues they see every day in the news, providing them with a comprehensive description of the social demography of the American family. Understanding ever-changing family systems and patterns requires taking the pulse of contemporary family life from time to time. This book paints a portrait of family continuity and change in the later half of the 20th century, with a focus on data from the 1970's to present. The authors explore such topics as the growth in cohabitation, changes in childbearing, and how these trends affect fam.